Endogenous money: Structuralist and horizontalist - L. Randall Wray (Levy Economics Institute of Bard College, 2007)
While the mainstream long argued that the central bank could use quantitative constraints as a means to controlling the private creation of money, most economists now recognize that the central bank can only set the overnight interest ratewhich has only an indirect impact on the quantity of reserves and the quantity of privately created money. Indeed, in order to hit the overnight rate target, the central bank must accommodate the demand for reserves, draining the excess or supplying reserves when the system is short. Thus, the supply of reserves is best characterized as horizontal, at the central bank's target rate. Because reserves pay relatively low rates, or even zero rates (as in the United States), banks try to minimize their holdings. Over time, they continually innovate, as they seek to minimize costs and increase profits. This includes innovations that reduce the quantity of reserves they need to hold (either to satisfy legal requirements, or to meet the needs of check cashing and clearing), and also innovations that allow them to increase the rate of return on equity within regulatory constraints, such as those associated with Basle agreements. Such behavior has been a central concern of the structuralist approachwhich argued that it is too simplistic to hypothesize simple horizontal loan-and-deposit supply curves.
Keywords: B5; E0; E4; E5; 330; Monetary Theory and Policy; Horizontalist; Strucuralist; Money Supply; Central Bank Targets; Central Bank Independence